Revisiting growth accounting from a trade in value-added perspective - Hubert Escaith (World Trade Organization (WTO), 2016)
Global Manufacturing and International Supply Chains changed the way trade and international economics are understood today. The present essay builds on recent statistical advances to suggest new ways of looking at the demand and supply side approaches when Global Value Chains (GVCs) - articulating supply and demand chains from an international perspective - are taken into consideration. This pilot case focuses on the G-20 countries, a group of leading developed and developing economies which took a prominent role in fostering and managing global economic governance. The paper is organised into two independent parts. The demand dynamics is first analysed through a growth-accounting decomposition, then through the long term determinants of income elasticity of imports. The second part looks at the implications of global manufacturing for our understanding of the supply-side growth dynamics, privileging a trade perspective: the definition of comparative advantages and the potential for value-chain upgrading.
Keywords: C18; C67; F14; F19; F43; F63; O11; O19; O41; O47; O57; 330; global value chains; trade and development; growth accounting; import elasticity; revealed comparative advantages; competitiveness benchmarking